POP-UP CARDS FOR EARLY CHILDHOOD LEARNING - Marlina Shinta Putri; Siti Wahyuningsih; Ruli Hafidah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this study is to apply pop-up card in early childhood learning. This research used qualitative approach. The subjects in this research were children aged 4-5 years. Data collection techniques were conducted through interviews, observation, and documentation. Technique of validity test of qualitative data used triangulation technique and triangulation of source. The analysis technique for qualitative data used    interactive model. The stages of application of pop-up card for early childhood learning include: (1) preparation stage, (2) implementation stage, and (3) the closing stage. The benefits of the application of pop-up cards for early childhood learning include: to facilitate the child in understanding the learning materials and make it easier for children to recognize letters and tell stories.